V144D Mutation of SPTLC1 Can Present with Both Painful and Painless Phenotypes in Hereditary Sensory and Autonomic Neuropathies Type I - Kwo Wei David Ho; Nivedita U. Jerath (Case Reports in Genetics)
Hereditary sensory and autonomic neuropathy type I (HSAN I) is an autosomal dominant disease characterized by distal sensory loss, pain insensitivity, and autonomic disturbances. The major underlying causes of HSAN I are point mutations in the SPTLC1 gene. Patients with mutations in the SPTLC1 genes typically exhibit dense sensory loss and incidence of lancinating pain. Although most of these mutations produce sensory loss, it is unclear which mutations would lead to the painful phenotype. In this case series, we report that the V144D mutation in SPTLC1 gene may relate to both painful and painless peripheral neuropathies. The unique clinical phenotype of this mutation may guide clinical workup and treatment for patients with painful and painless neuropathies.